N SOMEWHAT #REGULAR GENERALIZED-CONTINUOUS FUNCTIONS AND SOMEWHAT #REGULAR GENERALIZED-IRRESOLUTE FUNCTIONS IN TOPOLOGICAL SPACES - Hammed, Dunya Mohamed; Hamdi, Sanaa (MAGISTRA, 2015)
Abstract: In this paper, we introduce a new type of somewhat continuous functions called (somewhat #regular generalized-continuous functions and somewhat #regular generalized- irresolute functions) . Also , will be given the relationships of these functions with some other somewhat continuous functions in topological spaces . Furthermore , will be study and proved some of their properties